Effectiveness of Ballast Water Management for Marine Biota Conservation in Indonesia - Ridho Apriansyah; K.P. Suharyono S. Hadiningrat; Febri Pramudya Wardani (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
The implementation of ballast water management in Indonesia still faces significant challenges, despite efforts to adopt international standards as regulated by the International Maritime Organization (IMO). The main challenges include infrastructure limitations, lack of supervision and law enforcement, limited human resources, and high implementation costs. Consequently, the risk of invasive species entering through ballast water remains high and threatens Indonesia's marine ecosystem. To address these issues, strategic measures are needed, such as infrastructure development, strengthening supervision and law enforcement, enhancing human resource capacity through regular training, providing economic incentives, and reinforcing international cooperation. The implementation of these strategies is expected to improve the effectiveness of ballast water management, thereby supporting the preservation of marine ecosystems and the sustainability of Indonesia’s maritime environment.